Life over limb: Arterial access-related limb ischemic complications in 48-hour REBOA survivors. Issue 4 (15th April 2022) - Laverty, Robert B.; Treffalls, Rebecca N.; McEntire, Shane E.; DuBose, Joseph J.; Morrison, Jonathon J.; Scalea, Thomas M.; Moore, Laura J.; Podbielski, Jeanette M.; Inaba, Kenji; Piccinini, Alice; Kauvar, David S.
Abstract : Arterial access for #REBOA comes at the risk of limb #ischemia. We use #AAST #AORTA multicenter registry data to determine risk factors for access-related limb ischemic complications in REBOA survivors. Abstract : BACKGROUND: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is increasingly used in some trauma settings. Arterial access-related limb ischemic complications (ARLICs) resulting from the femoral arterial access required for REBOA are largely under reported. We sought to describe the incidence of these complications and the clinical, technical, and device factors associated with their development. METHODS: This was a retrospective cohort study of records of adult trauma patients from the American Association for the Surgery of Trauma Aortic Occlusion for Resuscitation in Trauma and Acute care surgery registry between October 2013 and September 2020 who had REBOA and survived at least 48 hours. The primary outcome was ARLIC, defined as clinically relevant extremity ischemia or distal embolization. Relevant factors associated with ARLIC were also analyzed. RESULTS: Of 418 identified patients, 36 (8.6%) sustained at least one ARLIC; 22 with extremity ischemia, 25 with distal embolism, 11 with both. Patient demographics and injury characteristics were similar between ARLIC and no ARLIC groups. Access-related limb ischemic complication was associated with larger profile devices ( p = 0.009), cutdown access technique ( p = 0.02), and the presence of a pelvic external fixator/binder ( p = 0.01). Patients with ARLIC had higher base deficit ( p = 0.03) and lactate ( p = 0.006). One hundred fifty-six patients received tranexamic acid (TXA), with 22 (14%) ARLICs. The rate of TXA use among ARLIC patients was 61% (vs. 35% TXA for non-ARLIC patients, p = 0.002). Access-related limb ischemic complication did not result in additional in-hospital mortality, however, ARLIC had prolonged hospital LOS (31 vs. 24 days, p = 0.02). Five ARLIC required surgical intervention, three patch angioplasty (and two with associated bypass), and four ARLIC limbs were amputated. CONCLUSION: Femoral artery REBOA access carries a risk of ARLIC, which is associated with unstable pelvis fractures, severe shock, and strongly with the administration of TXA. Use of lower-profile devices and close surveillance for these complications is warranted in these settings and caution should be exercised when using TXA in conjunction with REBOA. LEVEL OF EVIDENCE: Prognostic and Epidemiologic, Level III Abstract :